Research on the National New Energy Strategy From the Perspective of Political Economics - Pan, Hao; Xu, Shichang; Wang, Zidi; Liang, Zijian; Zeng, Lingdong (Frontiers in Energy Research, 2021)
Based on the perspective of political economics analysis, this article conducts research on the national new energy strategy as the economic situation changes differently from the past. Under the socialist market economy system with Chinese characteristics, the new energy strategy is not only an inevitable choice for China as a responsible major country, but also a key measure to promoting high-quality economic development. Through the analysis of the main dilemmas faced by China's implementation of new energy strategy, this article proposes to design policies in terms of core technology research, innovative industry financing, cultivating professional talents, and continuous expansion of opening up, to originate a high-quality development path for China.